Assessment of Cardiovascular Risk in Hospitalized Patients with Hypertension Aged 40 and Over - Joana Simeonova; Snejanka Tisheva-Gospodinova; Yoana Todorova; Petkana Hristova; Asia Yanakieva; Martin Hristov (Journal of Biomedical & Clinical Research, 2017)
The aim of the cross-sectional study was to estimate the absolute 10-year risk for fatal cardiovascular disease (CVD) in patients with hypertension by Systematic Coronary Risk Estimation (SCORE). The study was carried out in 2016 as part of Project No 4/2016. Ninety-one patients aged 40-89 years were included. The mean age of the sample was 66.0±11.0, and 44.0% were males. Information of the patients’ risk profile included about age, gender, blood pressure, smoking and total cholesterol. The patients with hypertension were stratified according to a 10-year absolute risk of CVD. Data were processed by Statistical Package for Social Science versions 19.0 (SPSS.v.19.0). Over two-thirds of the patients had 1 stage hypertension (31.9%) and 2 stage hypertension (37.4%). Median systolic blood pressure on admission to the clinics was 160 mg Hg, and median diastolic blood pressure was 90 mm Hg. Total serum cholesterol values exceeded 4.9 mmol/L in 64.0% of the patients. Smokers accounted for about one-fourth of the patients, most of them having smoked for 40 years. The mean number of risk factors for CVD was 3.0. Over 65% of the patients were found to be at a very high 10-year absolute risk of fatal CVD by SCORE. Cardiovascular risk assessment has important role in prevention of morbidity, premature death and disability of CVD.